Comparative Study of Some Virulence Factors and Analysis of Phylogenetic Tree by 16S rDNA Sequencing of Aeromonas hydrophila Isolated from Clinical and Environmental Samples - Abdulhasan, Ghusoon A.; Alattar, Nagham S.; Jaddoa, Nihad T. M. (Iraqi Journal of Science, 2019)
Aeromonas hydrophila is widely distributed throughout the world and causes diseases to animals and human exposed to contaminated environments such as water and soil. This study aimed to compare between isolates of A. hydrophila collected from clinical and environmental samples, through investigating the phenotype of some virulence factors in vitro, including hemolysin, protease, lipase, nuclease and biofilm formation ability. Also, the antimicrobial susceptibility for different antibiotics was determined using disc diffusion method. For genotypic identification of isolates and phylogenetic tree construction, 16S rDNA target gene was amplified and sequenced. The phenotypic results showed some differences between the isolates (clinical and environmental). All isolates were resistance to clindamycin, amoxicillin and erythromycin while susceptible to gentamicin, amikacin and vancomycin. Sequences of 16S rDNA confirmed the identification of the studied bacteria as A. hydrophila with 99-100% , and identity and phylogenetic tree by neighbor-joining clearly separated the isolates in a branching pattern which displayed similarity to the GenBank isolates obtained from Asian regions. The clinical isolates showed less polymorphism than the environmental isolates.